Risk Factors of Anastomotic Leakage After Esophagectomy With Intrathoracic Anastomosis - Li, Huan; Zhuang, Shimin; Yan, Honghong; Wei, Wenxiao; Su, Quanguan (Frontiers in Surgery, 2021)
Purpose: Anastomotic leakage is one of the most common complications of esophagectomy, it serves as one of the main causes of postoperative death of esophageal cancer. It is of clinical significance to try to discover the risk factors that cause anastomotic leakage. Methods: This retrospective study was conducted on 1,257 consecutive esophageal cancer patients who underwent esophagectomy with intrathoracic anastomosis from January 2010 to December 2015 at a high volume cancer center. Multivariate Logistic Regression analysis, Spearman rank correlation analysis, Mann-Whitney U test and Kruskal-Wallis test were performed to identify the risk factors to the occurrence of anastomotic leakage and the length of hospital stay. Results: Intrathoracic anastomotic leakage occurred in 98 patients (7.8%). Older patients were more likely to develop anastomotic leakage. Patients with diabetes had a higher leakage rate. Intrathoracic anastomotic leakage, old age as well as comorbidities were associated with longer hospital stay. Conclusion: Our study suggested that old age and diabetes were risk factors to intrathoracic anastomotic leakage. In-hospital stay would be lengthened by intrathoracic anastomotic leakage, old age and comorbidities.